Comparison of antigenic heterogeneity of Neisseria gonorrhoeae strains by micro-immunofluorescence and serum bactericidal tests. - Mark, J A (1978)
The antigenic heterogeneity of Neisseria gonorrhoeae strains was assessed by the micro-immunofluorescence (micro-IF) and the serum bactericidal tests. The micro-IF test verified the antigenic heterogeneity of nine strains received from the Center for Disease Control and placed them into immunotypes A and B. The serum bactericidal system also detected different antigenic determinants among the strains. Although the micro-IF and bactericidal assays did not correspond in each instance, the overall pattern of similarities and differences among these gonococcal strains was similar. The micro-IF pattern obtained with mouse antisera was identical to the pattern revealed with guinea pig antisera. Different colony type organisms showed similar sensitivity in the bactericidal test. The micro-IF test is a rapid technique for the immunotyping of N. gonorrhoeae and has the additional advantages of reproducibility and simplicity.